Potential of Art Classes in Preparing Adolescents and Youth to Participation in Festivals - RADOMSKAYA, Olga Igorevna; BOYAKOVA, Ekaterina Vyachslavovna; SITNIKOV, Philipp Sergeevich (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article aims to determine whether art classes during the educational process and free time prepare students for participation in festivals and to identify the preferences of adolescents and youth in art. A comparative study was conducted using a non-personified online survey of adolescents and youth aged from 12 to 21 years old from three European countries. The study identified the content of preferences in the choice of free-time activities and various art hobbies in youth regardless of the country of residence. It was found that the potential of participating in a festival is based on the preference of a certain type of art and the desire to share one’s achievements with peers. RESUMEN El artículo tiene como objetivo determinar si las clases de arte durante el proceso educativo y el tiempo libre preparan a los estudiantes para participar en festivales e identificar las preferencias de los adolescentes y jóvenes en el arte. Se realizó un estudio comparativo utilizando una encuesta en línea no personificada de adolescentes y jóvenes de 12 a 21 años de tres países europeos. El estudio identificó el contenido de preferencias en la elección de actividades de tiempo libre y varios pasatiempos artísticos en la juventud, independientemente del país de residencia. Se descubrió que el potencial de participar en un festival se basa en la preferencia de cierto tipo de arte y el deseo de compartir los logros de uno con sus compañeros.